2021
DOI: 10.7759/cureus.16722
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Association Between Schizophrenia and Substance Use Disorder-Predictors, Mechanisms and Treatment Modifications: A Systematic Review

Abstract: Individuals with schizophrenia are particularly vulnerable to substance abuse problems. Comorbidity with substance use disorders (SUDs) frequently results in early death and increased dysfunction observed in schizophrenia. This dual diagnosis can be explained through multiple general mechanisms. Tobacco, alcohol, cannabis, and cocaine are substances widely used by individuals with schizophrenia. This study highlights the predictors, mechanisms responsible for the relationship between substance use disorder and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Hence, data regarding benzodiazepines should be treated with particular caution in this case. We also found a relationship between cannabis use and the occurrence of disorders from the F20–F29 group, which is well-documented in the literature 6 , 7 , 21 , 22 . The literature also provides data on the relationship between COC use and the occurrence of disorders from the F20–F29 group 22 .…”
Section: Discussionsupporting
confidence: 83%
“…Hence, data regarding benzodiazepines should be treated with particular caution in this case. We also found a relationship between cannabis use and the occurrence of disorders from the F20–F29 group, which is well-documented in the literature 6 , 7 , 21 , 22 . The literature also provides data on the relationship between COC use and the occurrence of disorders from the F20–F29 group 22 .…”
Section: Discussionsupporting
confidence: 83%
“…Additionally, comorbid substance use, and cannabis use in particular, can worsen adherence to antipsychotics [182][183][184] . All these factors point to the need to screen for and address substance use disorders as early as possible when treating patients with schizophrenia 185,186 .…”
Section: Discussionmentioning
confidence: 99%
“…The case of Syd Barrett, the frontman of Pink Floyd who purportedly left the band due to the development of schizophrenia precipitated by excessive LSD use, may further illustrate this potential relationship between chronic LSD exposure and psychosis (Fusar-Poli, 2007). However, it is worth mentioning these cases were likely confounded by use of cannabis, which is a well-known risk factor for development of schizophrenia (Masroor et al, 2021), and has also been shown to alter dopaminergic signaling in the striatum (Sami et al, 2015), including the associative striatum (see Sami et al, 2015, for a review) which is widely implicated in psychosis (Conn et al, 2020). Further complicating the picture, first generation antipsychotics, with significant antidopaminergic action, were tried in three of the four cases of LSD-induced psychosis and found to be ineffective (Glass and Bowers, 1970).…”
Section: Chronic Lsd Administration: a True Psychotomimetic?mentioning
confidence: 99%